La adaptación social en el ámbito educativo y su relación en el consumo de alcohol y nicotina en los estudiantes de bachillerato de la Unidad Educativa Marista del cantón Macará periodo 2015 -2016. - Arévalo Espinoza, Giancarlo Alexander (2016)
The present research aims to determine the social adaptation in alcohol consumption and nicotine in the high school students of the Marist Educational Unit of the Canton Macara; To discriminate through the Magellan Scales of Adaptation, the types of adaptation maintained by the students; To investigate types of social adaptation more tending to the consumption of alcohol and nicotine; To specify the relation of the types of social adaptation and consumption of alcohol and nicotine in the educational field; The research is descriptive with a quantitative-qualitative approach, cross-section; Information was collected from 90 students of the Secondary School of the Marist Education Union of the Canton Macara; The instruments of data collection used were: Adaptation Questionnaire that quantitatively determined the levels of adaptation of the subject and the Test of detection of alcohol consumption, tobacco that established the level of use of alcohol and nicotine; We can mention that the students have a good academic adaptation with 22.2%; The main reason adolescents consume alcohol and nicotine is the low degree of personal adaptation with 38.8%, the relationship of personal adaptation and use of alcohol and nicotine in the educational field with 36.6%; Developed a psychoeducational plan aimed at preventing the consumption of alcohol and nicotine; Improving learning in the educational field while maintaining adequate social adjustment. Keywords: Social Adaptation, Alcohol, Nicotine.